Franchise Business Strategy Playgroup, Kindergarten And Day Care In Cerdas Ceria By Using Qspm And Benchmarking Method - Mochamad Rizky Fauzy; Budi Praptono; Ima Normalia Kusmayanti (eProceedings of Engineering, 2019)
Abstract Cerdas Ceria School is an educational institution in the field of early childhood education located on Jl. Trs. Martanegara No.22, Bandung. The competitiveness in the field of education requires schools expand the right business strategy to improve the anality. This study analyzed and formulated the right franchise business strategy for Cerdas Ceria School. The approach used in determining the right franchise business strategy is the Quantitative Strategic Planning Matrix (QSPM) method. The stages of this study begin with the identification of external and internal factors of the school and their effects on the strategy formulation process in the form of weighting results on EFE matrix and IFE matrix. Based on the results of the total weighting of EFE matrix and IFE matrix, it was discovered that the company's position was based on the external and internal factors of the school in the Internal-External (IE) matrix which served as the basis for formulating alternative strategies on the SWOT matrix. Then QSPM analysis was applied to evaluate several alternative strategic choices objectively to get the best strategy. The QSPM matrix was also able to decide the best priority strategy. The franchise design was made using benchmarking methods as the basis of a franchise cooperation program for Cerdas Ceria School.Keywords: Franchise Business Strategy, EFE Matrix, IFE Matrix, IE Matrix, SWOT Matrix, QSPM, Benchmarking